Article RETRACTED due to manipulation by the authors Comparación de los niveles de ansiedad de deportistas individuales y grupales (Comparison of anxiety levels of individual and group athletes): Article RETRACTED due to manipulation by the authors - Pranoto, Nuridin Widya; fauziah, varhatun; Ockta, Yovhandra; Zarya, Fiky; Iswanto, Ari; Hermawan, Hedi Ardiyanto; Fitriady, Gema; Orhan, Bekir Erhan; Karaçam, Aydın; Adıgüzel, Niyazi Sıdkı (Retos, 2024)
Kaygının incelenmesi, özellikle de sosyodemografik değişkenlerle olan ilişkisi, spor psikolojisi araştırmalarında verimli olmuştur. Bu çalışma, sporcuların kaygılarının cinsiyet farklılıkları ve yapılan spor türü (bireysel/grup) değişkenleri ile karşılaştırılmasını belirlemeyi amaçlamaktadır. Yapısal eşitlik modellemesi uygulaması 80 Endonezyalı sporcu üzerinde gerçekleştirilmiştir. Bu sayının 40'ı (%50) kadın, 40'ı (%50) erkek sporculardan oluşmaktadır. Sporcular çeşitli bireysel sporlarda (yüzme, kaya tırmanışı; %50) ve takım sporlarında (basketbol, voleybol; %50) yarışmaktadır. Sporcuların yaşları 20-25 arasında değişmektedir (M = 22 yıl; SD = 4.99). Cinsiyet ve spor türü (bireysel ve takım) arasında birinci ve ikinci dereceden modellerin ölçüm değişmezliğini test ettikten sonra, örtük ortalama karşılaştırmaları araştırılmış ve uygun etki büyüklüklerini elde etmek için (Cohen Day 1988) istatistikleri hesaplanmıştır (Kline, 2016). Erkek ve kadın sporcular arasında ve ayrıca bireysel ve takım sporları arasında anlamlı farklılıklar tespit edilmiştir. Kadın ve bireysel spor yapan sporcuların genel spor kaygısı düzeyleri daha yüksektir. Bu çalışmanın sonuçları, kaygının sporcular tarafından cinsiyete ve spor türüne göre farklı değerlendirildiğine dair kanıtlar sunmaktadır.Palabras clave: Sporcu kaygısı; sporda cinsiyet farklılıkları; bireysel ve takım sporları; spor psikolojisi araştırmaları; sporda yapısal eşitlik modellemesi; Abstract. The study of anxiety, particularly its relationship to sociodemographic variables, has been fruitful in sport psychology research. This study aims to determine the comparison of athletes' anxiety with the variables of gender differences and the type of sport played (individual/group). The application of structural equation modeling has been carried out on 80 Indonesian athletes. Of this number, 40 (50%) are female athletes and 40 (50%) are male athletes. They compete in a variety of individual sports (swimming, rock climbing; 50%) and team sports (basketball, volleyball; 50%). Athletes' ages ranged from 20-25 years (M = 22 years; SD = 4.99). After testing the measurement invariance of the first- and second-order models, across gender and sport type (individual vs. team), latent mean comparisons were investigated and statistics were calculated to obtain appropriate effect sizes. Significant differences were detected between male and female athletes as well as between individual and team sports. Female and individual sports athletes have higher levels of general sports anxiety. The results of this study provide evidence that anxiety is assessed differently by athletes based on gender and type of sport.Keywords: Athlete anxiety; gender differences in sports; individual vs. team sports; sports psychology research; structural equation modeling in sports;